Dietary Copper Intake and Its Association With Telomere Length: A Population Based Study - Lin, Zhu; Gao, Hongmei; Wang, Bing; Wang, Yongqiang (Frontiers in Endocrinology, 2018)
Background Telomere is regarded as the fundamental aspect of aging and copper is recognized as an essential trace element. The role of copper in telomere length maintenance is seldom examined. This study aims to investigate if telomere length is associated with dietary copper intake. Methods We used data from a large community-based population study. The association between telomere length and dietary copper intake was assessed using multiple linear regression models. We also examined if obesity, measured by body mass index could affect this observed association. Results There are 7324 participants had both telomere length measured and dietary copper intake assessed, around 48.0% of them were men. Telomere length was longer in women than that in men (1.05 ± 0.26 vs. 1.00 ± 0.26 T/S ratio), while dietary copper intake was less in women that that in men (1.12 ± 0.80 vs. 1.51 ± 1.61 mg). After controlling for age, sex, ethnicity, and body mass index in the multiple linear regression models, one unit increase of log-transformed dietary copper intake was significantly associated with longer telomere length (β=0.02, 95% confidence interval: 0.01, 0.04). We did not find a significant sex difference for this association. Conclusions Dietary copper intake was significantly associated telomere length. The role of copper in human health might be involved in biological aging process.